LEGAL PRINCIPLES OF ADMINISTRATIVE ACTIVITY AND ADMINISTRATIVE JUDICIARY IN UKRAINE - Kunev, Yurii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is to analyze and reveal the problems of theoretical and practical plan and prospects for the development of legal regulation of administrative activities through the prism of defining and implementing basic legal principles. Research methods: a comprehensive approach to creating a theoretical picture of the object and the application of the methodological scheme of «double knowledge» about the object as such and the knowledge that describes and depicts it; comparative legal and doctrinal knowledge of administrative law, as well as the method of generalization and modeling of new theoretical knowledge of administrative law. Results: problems of further development of theory and practice of administrative law are identified and a theoretical approach to their solution is proposed. It is established that the system of administrative and administrative-judicial activities requires an appropriate system of legal principles, which should be the legal basis and basis for the effective functioning of these activities in an inseparable relationship, which will ensure the rights and legitimate interests of citizens of Ukraine. Human rights and fundamental freedoms, equal. In the absence of the integrity of such a system at the level of principles (law, administrative law, administrative procedure) there is a gap as legal support for the implementation of constitutional principles embodied in the norms of administrative law - norms-standards for public administration. Discussion: argues that the practical implementation of approaches based on the construction and implementation of a system of legal principles for regulating administrative activities and administrative judicial activity, effective for the transition of administrative law of Ukraine to the stage of «traditional».